Money and the Pursuit of Happiness: In Good Times and Bad - Erika Rasure (Journal of Financial Therapy, 2011)
Money and the Pursuit of Happiness: In Good Times and Bad is a consumer’s introductory guide of personal reflection with money. The book’s author discusses how to develop a foundational relationship with one’s financial self in an effort to establish ongoing happiness and life satisfaction. The book can be an effective resource recommended by financial and mental health practitioners to clients. The book can help introduce or guide ongoing discussions about who an individual is in relation to money. In addition, this book offers a variety of real-life examples and exercises for readers, providing an opportunity to gain insight into their financial personalities.
Keywords: financial therapy; financial counseling; marriage and family therapy; psychology